Allies and adversaries : the Joint Chiefs of Staff, the Grand Alliance, and U.S. strategy in World War II - Stoler, Mark A. (University of North Carolina Press, 2000)
"Drawing on sources that include the unpublished records of the Joint Chiefs as well as the War, Navy, and State Departments, Mark Stoler analyzes the wartime rise of military influence in U.S. foreign policy. He focuses on the evolution of and debates over U.S. and Allied global strategy. In the process, he examines military fears regarding America's major allies - Great Britain and the Soviet Union - and how those fears affected President Franklin D. Roosevelt's policies, interservice and civil-military relations, military-academic relations, and postwar national security policy as well as wartime strategy"--Jacket.